Pengaruh Penggunaan Multimedia Interaktif Terhadap Kemampuan Penalaran Matematis Peserta Didik Pada Materi Prisma - Khaerani Khaerani; Sumarno Ismail; Franky Alfrits Oroh (Universitas Negeri Gorontalo, 2022)
This study aims to examine the effect of interactive multimedia on students' mathematical reasoning abilities on prismatic material. This research is a quasi-experimental study with a post-test-only control group design. Students in one of the junior high schools in Gorontalo were the samples in this study, where class VIII-2 was the experimental class, and class VIII-1 was the control class. The experimental class was a class that was given learning treatment using interactive multimedia, and the control class was a class that was given learning treatment using PowerPoint. Data on students' mathematical reasoning abilities were collected by giving tests of mathematical reasoning abilities using questions in the form of descriptions. The data collected was then analyzed descriptively and inferentially. The results of the descriptive analysis obtained are the average mathematical reasoning ability of students in the experimental class is higher than the control class. These results are supported by the inferential analysis, which reveals that interactive multimedia has more effect on students' mathematical reasoning abilities than PowerPoint.